CORPORATE FINANCIAL ANALYSIS AND LOCALIZATION CRITERIA - EMERGING VERSUS DEVELOPED COUNTRIES: CASE STUDY ON IT COMMERCIAL COMPANIES - CRISTINA MARIA TRIANDAFIL; PETRE BREZEANU (Annals of the University of Petrosani: Economics, 2010)
This paper consists of a practical approach on corporate default valuation according to the localization criteria. There will be conducted a case-study on two samples of companies, one located into developed countries, the other into emerging countries, in order to highlight out potential differentiations in terms of corporate default assessment. The key concept is represented by the default point and its main drivers. The statistical perspective aims to reveal out both default point and corporate finance mechanisms characteristics according to the localization criteria.